Interactive Read Aloud Strategy in The Optimization of the Children's Fairy Talecomprehension Skills - Abbas, Sri Susilaningsih, Atip Nurharini, Nuraeni (Elementary School Teacher, 2018)
Research objectives, are: 1). Knowing the comprehension skills of fairy tale after the implementation of the strategy of interactive read aloud, 2) analyzes the changes in the behavior of students after learning of a fairy tale with a strategy of interactive read aloud, 3). Knowing the learning implementation strategy with interactive read aloud in the optimization of the students’ fairy tale comprehension skills.Sampling techniques in the research used random sampling by lot. The number of students who made the sample are 25 students. To obtain data and information relating to a matter which examined various ways is through observation, documentation, field notes and question form. Data analysis techniques used are analysis of Mix Methods qualitative and quantitative techniques.The results of the research are: children know fairy tale skills after the implementation of interactive read aloud strategy, by understanding reading, making predictions, making connections, summarizing, drawing conclusions with successful criteria; 2). Changes in student behavior after learning fairy tale with interactive read aloud strategy with excellent results, 3) .The implementation of learning with interactive read aloud strategy in the optimization of students' fairy tale skills can run very well and maximally.The conclusion of the research is the skill of fairy tale can be formed very well after the implementation of interactive read aloud strategy, the student behavior change can be formed well after the learning of fairy tale with interactive read aloud strategy, and the implementation of learning with interactive read aloud strategy can be done optimally with the teacher improve students' fairy tale skills. A suggestion in the study is that teachers should always introduce a fairy tale to the students to embedded good behavior.Keywords: Skills, understanding, fairy tale, interactive read aloud strategy